Molecular characterization of bacteria with probiotic potential isolated from stool of human neonates - Santos, Ricardo (2019)
The aim of this study is to molecularly characterize bacteria with probiotic potential isolated from feces of human neonates. Sixty stool samples from neonates (0-3 days) were evaluated and enriched in Man Rogosa and Sharp (MRS) broth at 37 ° C / 24h. It was selected and subjected to in vitro tests with bile salts, resistance to low pH and antimicrobial activity against Escherichia coli ATCC25922, E. coli ATCC35218, Salmonella enterica and Listeria inocua by agar diffusion assay. The molecular identification was made with PCR-BOX amplifications and the sequencing of the 16S rRNA gene. A total of 48 strains were isolated and all showed resistance to pH 3 and 0.3% bile salts; 3 strains showed antimicrobial activity against E. coli ATCC25922, 1 strain against E. coli ATCC35218, 5 strains against L. innocuous and all against S. enterica. Of the 48 strains, two BOX-PCR profiles belonging to the genera of Lactobacillus and Enterococcus were obtained. Nine strains (C52, C61, C71, C112, C162, C192, C20, C35, and C42) presented 100% similarity to L. plantarum ATCC 14917T [ACGZ01000098] and two strains (C15 and C40) 99.93% and 99.80 % similarity, respectively to Enterococcus faecium CGMCC 1.2136T [AJKH01000109]; these strains showed activity in milk with significant differences (p value <0.05) in the kinetics of pH 3. In conclusion, bacteria with probiotic potential were found.